Detection of Magnetic Field Effects by Confocal Microscopy - Déjean, V; Timmel, C; Konowalczyk, M (University of Oxford, 2020)
This dataset contains raw data and accompanying analysis used in the publication 'Detection of Magnetic Field Effects by Confocal Microscopy' by Dejean et al. The data was recorded using a Zeiss inverted confocal microscope - Exciter 5. The analysis scripts are written in Matlab (R2017b). Please note that the analysis shown here is a simplified version of the code used for the publication and is only meant to showcase the methods used. Pairs of paramagnetic species generated under conservation of total spin angular momentum can undergo magnetosensitive processes. Two prominent examples of systems exhibiting these so-called magnetic field effects (MFEs) are photogenerated radical pairs created from molecular precursors and pairs of triplets generated by singlet fission. Here, we showcase confocal microscopy as a powerful technique for the investigation of such phenomena. We first characterise the instrument studying the field-sensitive chemistry of two systems in solution: radical pairs formed in the protein cryptochrome and the flavin mononucleotide/hen-egg white lysozyme model system. We then extend these studies to single crystals. Firstly, we report temporally- and spatially-resolved MFEs in flavin-doped lysozyme single crystals. Anisotropic magnetic field effects are then reported in tetracene single crystals. Finally, we discuss the future applications of confocal microscopy for the study of magnetosensitive processes with a particular focus on the cryptochrome-based chemical compass believed to lie at the heart of animal magnetoreception.